Pediatric laparoscopic pieloplasty - Morao, Sofia (2017)
Introduction: Ureteropelvic junction obstruction (UPJO) is the most common congenital cause of upper urinary tract obstruction in children. Our objective is to report our experience concerning the first 20 laparoscopic pyeloplasties. Material and methods: Retrospective study including twenty children with diagnosis of UPJO that underwent laparoscopic pyeloplasty by a single surgeon, at our Hospital, between November 2010 and December 2014, with at least one year of follow-up. Success was defined as absence of conversion, resolution of symptoms and radiologic criteria improvement. Results: Median age at surgery was 9.5 years (range between 10 months and 17 years-old). Intrinsic obstruction was found in 7 cases, extrinsic obstruction in 12 cases and one case with both situations. Median operative time was 235 minutes (range between 165-275 minutes), with need for conversion in 2 cases (10%).  Median hospital stay was 2 days (range between 2-5 days. Four patients (20%) had early postoperative complications and two cases (10%) needed surgical revision during follow-up. Median follow-up time was 33 months (range between 12-60 months). In follow-up, all but two patients were asymptomatic. There was radiologic improvement of hydronephrosis in all patients but one, although he had non-obstructive pattern in renographic drainage. Conclusion: Our results are similar to those found in literature, with success rates comparable to open pyeloplasty with advantages of minimally invasive surgery.